Impaired Mobility in Intellectually Disabled Patients: A Single-Centre Study from Saudi Arabia - Tabassum Alvi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: People with impaired mobility have higher rates of morbidity, disability, and mortality. Patients with impaired mobility as well as having intellectual disabilities can face more challenges in compensating for a mobility limitation. In KSA, individuals with disabilities constitute 7.1% of the total population. The objectives of our study were to find out (1) The prevalence of impaired mobility among ID patients (2) The association between gender and age of ID patients with impaired mobility (3) The association between ID and impaired mobility in the study population. Methodology: A Cross-sectional observational study was conducted on 147 patients admitted with intellectual disability in Rehabilitation Center Majmaah, Saudi Arabia. Data was collected using pre-designed research tools from the clinical records regarding the level of disability and impairment in mobility. All the data was entered in the SPSS software 23 and statistical analysis was done. A 95% degree of freedom with a p-value of<0.05 was considered statistically significant. Results: Out of 147 patients, 102 (69.38%) patients had impaired mobility. Out of 102 patients, 24(23.07%) patients had mild difficulty,16(15.68%) patients could walk with support and 62 (60.78%) patients were completely bedridden. More than half, about 63(61.76%) were males and 39 (38.23%) were females. Most of them were in an age range of 11yeras to 40 years. A statistically significant association was found between age and impaired mobility for patients who were mobile with support(p=0.05) and those who were completely bedridden (p=0.044) respectively. A significant association was also found between the impairment in mobility and the severity of ID (p<0.001). Conclusion: There was a male preponderance (almost twofold at all levels of mobility limitation) in ID patients in our study population. About two-thirds of the patients with impaired mobility were bed-ridden. All patients with profound ID and about one-third of patients (30%) with severe ID were bedridden.